The theoretical foundations of formation of professional competence in future medical specialists - Radziievska, Iryna (ScienceRise: Pedagogical Education, 2017)
The article presents the theoretical analysis of psycho-pedagogical literature about the problems of professional training of medical specialists. It was elucidated, that the determination of theoretical and practical principles of their professional competence formation is an actual scientific direction of research. The notion “professional competence of medical specialists” is grounded; it is considered as integrative professional characteristic of a specialist. The reformation of educational system in Ukraine is a base of the national and spiritual regeneration of society, dignified education of new generation, movement of native science and technique towards the world standards and requirements. The educational progress and development is a base for successful formation of sovereignty and democratization processes of society in Ukrainian space and in conceptual sense – the advance of state for the sake of its future. The main aim of education development is a creation of conditions for personal development, creative self-realization of each Ukrainian citizen, generation of people, able to work effectively and study persistently during the whole life, protect and increase the ethical values and priorities of national culture and civic society, develop and strengthen the sovereign, independent, democratic, social and legal state as an inalienable component and embassy of European and world culture. The renewal of the essence of study is a determinative component of reformation of Ukrainian education and provides its correspondence with the modern needs of person and society